Identification and Prevalence of Ectoparasites in Carp (Cyprinus carpio) Seeds From Central Local Fish Seed Center and Fish Farmers in West Koya Region - Sahlan M Saleh (Journal of Aquaculture Development and Environment, 2021)
The needed for carp in Jayapura City was greatly increasing along with the high growth and increase of population in Jayapura City. Cultivation of carp (Cyprinus carpio) can be done intensively and semi-intensively by taking into account the economic value. However, from cultivation activities, the problems that were often faced in cultivation activities were the attack of dangerous types of pathogens such as parasites. Parasite was a fish disease that occurs more frequently. Parasites were organisms that live on the body of other organisms and generally have a negative effect on their host. This study aimed to identify and the prevalence of ectoparasites to determine the type and level of ectoparasite attack on carp (C. carpio) seeds and to reduce the impact of ectoparasites which was feared to reduce the amount of carp production from cultivation. The method used was a direct survey to the Local Fish Seed Center and fish farmers in the Koya Barat area. The fish used were carp in the seed phase where the fish's immune system was still weak, making it more susceptible to contracting parasites. This study showed that there were 4 types of parasites found during the study that infected carp seeds, namely Dactylogyrus sp, Gyrodactylus sp, Trichodina sp, and Lernea sp. The average prevalence rate of Dactylogyrus sp. at stations I, II, III, and IV was 25%, Gyrodactylus sp. 8.3%, Trichodina sp. 8.3% and Lernea sp. 5% with the lowest prevalence rate.